My donkey, my lover & I [videorecording (DVD)] - Calamy, Laure; Lavernhe, Benjamin, 1984-; Côte, Olivia; Vignal, Caroline; Vignal, Caroline (Greenwich Entertainment, 2022)
Antoinette, a schoolteacher, is looking forward to her long planned summer holiday with her married lover Vladimir, the father of one of her pupils. When she learns that Vladimir has to cancel because his wife organized a surprise hiking vacation, Antoinette decides to follow their tracks, accompanied by a protective donkey named Patrick.